2017
DOI: 10.18203/2349-2902.isj20174520
|View full text |Cite
|
Sign up to set email alerts
|

Oral premalignant lesions: a clinicopathological study

Abstract: Background: A significant number of oral cancer cases present initially with precursor lesions. If detected earlier in disease course it will reduce the morbidity and mortality. The objective of this study was to evaluate the clinical presentation and various histopathological types of premalignant lesions.Methods: This is descriptive, observational, analytical type of study of five-year duration. The detail clinical presentation, relevant investigation and histopathological study on biopsy tissue stain with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Our results were less compared to the corresponding values of 77.1% reported by Gupta et al 5 in Lucknow but distinctly higher than several other studies in India such as Saraswathi et al 6 We observed that highest number of PMD cases were in 50-60 yrs of age group (69.2%). This was comparable to the results from Kadashhetti et al 1 , Saraswathi et al 6 and Jagtap et al 10 . Several studies have reported equal prevalence of PMD among the middle aged and elderly subjects 8 whereas few others have reported highest prevalence in 21-30 years of age group 11 which was not in accordance with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Our results were less compared to the corresponding values of 77.1% reported by Gupta et al 5 in Lucknow but distinctly higher than several other studies in India such as Saraswathi et al 6 We observed that highest number of PMD cases were in 50-60 yrs of age group (69.2%). This was comparable to the results from Kadashhetti et al 1 , Saraswathi et al 6 and Jagtap et al 10 . Several studies have reported equal prevalence of PMD among the middle aged and elderly subjects 8 whereas few others have reported highest prevalence in 21-30 years of age group 11 which was not in accordance with our study.…”
Section: Discussionsupporting
confidence: 91%
“…According to Anna Starzyńska et al [15], the most common site involved was buccal mucosa (52.2%). Whereas buccal mucosa involvement was 55.26% in a study by Sunil Vitthalrao Jagtap et al [13].…”
Section: Resultsmentioning
confidence: 92%
“…Cessation of smoking habits may result in regression or even disappearance of the leukoplakia and diminish the risk of cancer development either at the site of the leukoplakia or elsewhere in the mouth or the upper aerodigestive tract. Sunil Vitthal Rao et al [13] mentioned that 68.41% of cases were leukoplakia followed by oral lichen planus (13.16%) oral submucous fibrosis (7.9%). According to Buoquot et al [14] leukoplakia is the most common cause.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Jagtap et al in their study found leukoplakia to comprise 68.41% of their study population. 11 As far as OSMF is concerned, a number of studies have reported it to be dominant premalignant type reporting in 30.4% to 88.1% of premalignant lesions. [12][13][14] In present study, majority of cases had involvement of multiple sites.…”
Section: Discussionmentioning
confidence: 99%